OPTIMALISASI KOMPETENSI BERBAHASA INGGRIS MELALUI PROGRAM PEMBELAJARAN BUSINESS ENGLISH BUAT SEKOLAH VOKASIONAL-ALMAKIYAH - Nurdiana, Nurdiana; Taufik, Alvin; Silalahi, Ronald Maraden Parlindungan (Universitas Bunda Mulia, 2022)
Vocational learning in Indonesia at the upper secondary level provides a large portion of improving English language skills. Besides being used as a compulsory subject/college in schools and universities, English lessons are studied in the context of vocational education to bridge the world of education with the needs of industry and the workforce on a national, multinational, and international scale. The high need for a competent workforce, which can be seen from the ability to speak English, presents a variety of specific subjects in line with this condition. The subject variant in question is business English or 'business English'. Referring to this condition and examining the need for vocational education, Community Service activities (ABDIMAS) are carried out with the theme 'Introduction to Business English'. ABDIMAS is held at the Almakiyah Vocational High School (SMK) in East Jakarta. ABDIMAS was carried out in response to the needs of partners who felt that the English learning materials did not meet the needs of students and graduates who were required to be absorbed in the world of work. ABDIMAS is carried out through three sessions of a hybrid online and offline enrichment program for students. Each session is taught about what aspects are included in business English and linguistic aspects commonly used in business and work contexts. This activity is oriented towards increasing the knowledge and insight of the participants regarding (i) business conversations, (ii) formal and informal expressions in business communication, (iii) basics of email writing. The activity ends with an evaluation that broadly shows that the activities are carried out in line with the work context so that they do not focus on the theoretical and implementation levels.